2020
DOI: 10.1039/d0cs00036a
|View full text |Cite
|
Sign up to set email alerts
|

Life and death of liquid-infused surfaces: a review on the choice, analysis and fate of the infused liquid layer

Abstract: We review the rational choice, the analysis, the depletion and the properties imparted by the liquid layer in liquid-infused surfaces – a new class of low-adhesion surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
264
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 263 publications
(265 citation statements)
references
References 330 publications
1
264
0
Order By: Relevance
“…A 5086 Al surface shows a WCA of 82.6 ± 5.7°, and a remarkably lower value of 44.2 ± 2.8° was measured on AAO surface. However, the WCA of the F‐AAO surface was 134 ± 6.2°, which was larger than that on the AAO surface, owing to the air remaining in the pores 34 . The contact angle of the SLIPS was 108.2 ± 1.8°.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…A 5086 Al surface shows a WCA of 82.6 ± 5.7°, and a remarkably lower value of 44.2 ± 2.8° was measured on AAO surface. However, the WCA of the F‐AAO surface was 134 ± 6.2°, which was larger than that on the AAO surface, owing to the air remaining in the pores 34 . The contact angle of the SLIPS was 108.2 ± 1.8°.…”
Section: Resultsmentioning
confidence: 90%
“…The equations are expressed as follows: ΔE1=EAE1=R()γBcosθBγAcosθAγAB>0 ΔE2=EAE1=R()γBcosθBγAcosθA+γAγB>0 where γ A , γ B , and γ AB are the surface tensions of the Liquid A (test liquid)–vapor interface, Liquid B (lubricating liquid)–vapor interface, and Liquid A–Liquid B interface, respectively. θ A is the WCA of Liquid A and θ B is WCA of Liquid B on a flat surface 12,32–34 . R represents the roughness factor, calculated by the WCA of by the WCA for a rough surface and a smooth surface ( R = cosθrcosθ) 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, SLIPS inspired by the slippery surface of Nepenthes has attracted tremendous amount of attention due to its superior water repellency. [ 115,116 ] First report by Aizenberg's group demonstrated that the presence of an immobilized liquid layer of fluorinated oil on polytetrafluoroethylene surface could significantly reduce biofilm attachment under static conditions or gentle flow. [ 117 ] Later they found similar trend in oil‐infused PDMS samples than noninfused ones.…”
Section: Biomimetic Antifouling Surface Technologiesmentioning
confidence: 99%
“…Due to concerns around the environmental safety and the high carbon footprint of the production of synthetic oils, plant oils such as argan oil, castor oil, or coconut oil have been considered as suitable candidates for the replacement. [ 115 ]…”
Section: Biomimetic Antifouling Surface Technologiesmentioning
confidence: 99%
“…[ 1–3 ] Inspired by the microstructured surface of the Nepenthes pitcher plant, LIS have a micro‐ and nano‐scale surface roughness which traps by capillarity a thin layer of an infused liquid, typically a lubricant. [ 3 ] The stable infusion with a lubricant is related to low values of droplet roll‐off angle (≤5°) and low contact‐angle hysteresis (≤5°), which typically result in low adhesion of aqueous solutions and most other liquids incompatible with the lubricant. As a result, LIS have antiadhesive and self‐cleaning properties and repel most types of fouling, including micro‐organisms (bacteria [ 4–6 ] ).…”
Section: Introductionmentioning
confidence: 99%